Pelatihan Penerapan Teknik Pernapasan Buteyko terhadap Pengontrolan Asma di Kelurahan Kalidoni Palembang - Utama, Yofa Anggriani (Universitas Baiturrahim, 2024)
Asthma is a chronic inflammatory disorder of the respiratory tract that involves many inflammatory cells such as eosinophils, mast cells, leukotrienes and others. This chronic inflammation is associated with airway hyperresponsiveness which causes repeated episodes with additional wheezing, shortness of breath, chest tightness and coughing, especially at night and in the morning. The aim of implementing this community service activity is to increase community knowlegde on how to control recurrence of asthma using the buteyko breathing technique. The implementation method is by providing health education and training on the buteyko breathing technique. The activity was attended by 15 people with asthma. Using a questionnaire, it was found that 3 participants (20%) had good knowledge of the buteyko breathing technique. After being given health education, there was an increase in knowledge, as many 11 participants (73%) had good knowledge of buteyko breathing technique